Application analysis: Theory of constraints for job scheduling on volunteer grid resources - Rubab, S. (American Scientific Publishers, 2016)
The Theory of Constraints (TOC) rules are applied for job scheduling on volunteer grid resources to investigate the constraint scheduling. TOC have been used in different flow processes which depend on multiple operating conditions. The job scheduling on volunteer grid resources is more complex because of unpredictable nature of resources and jobs. The TOC rules can be applied to solve the complex job scheduling on volunteer grid resources. The paper provides TOC application analysis using a detailed case study. The findings derived from case study suggest that TOC rules can be applied in its true nature, however a few modifications in TOC rules can better assist in solving complex job scheduling problem. Â© 2016 American Scientific Publishers. All rights reserved.